The dark side of the enlightenment - Fleming, John V. (Norton, 2013)
In The Dark Side of the Enlightenment John V. Fleming shows how the impulses of the European Enlightenment generally associated with great strides in the liberation of human thought from superstition and traditional religion were challenged by tenacious religious ideas or channeled into the darker pursuits of the esoteric and the occult. His topics include the stubborn survival of the miraculous the Enlightenment roles of Rosicrucianism and Freemasonry and the widespread pursuit of magic and alchemy
9780393079463
Keywords: Enlightenment; Occultism; Alchemy; Mysticism; Supernatural; Science